Korelasi Penghasilan Orang Tua terhadap Kualitas Hidup Anak yang Mengalami Talasemia Mayor - Tuti Asrianti Utami; Lina Dewi Anggraeni (Faletehan Health Journal, 2023)
Thalassemia requires prolonged care and treatment; so that it has an impact on the quality of life of the children. The quality of life of the children can include the subjective evaluation of positive and negative aspects of their life. This study aims to analyze factors related to the quality of life of children with thalassemia major. It was a quantitative study with a cross-sectional approach and conducted at Gatot Subroto Hospital and Harapan Kita Hospital in Jakarta. The number of samples were 83 respondents selected by using purposive sampling. The results based on chi-square test analysis explained that there was a significant relationship between children age (p-value 0.031), sex (p-value 0.001), children education (p-value 0.006), parents age (p-value 0.050), parity (p-value 0.00) and parental income (p-value 0.000) with the quality of life of children suffering from thalassemia major. The analysis of binary logistic regression tests found a positive relationship between parental income >regional minimum wage and the quality of life of children suffering from thalassemia major as much as 10.507 times more effectively than parental income less than regional minimum wage. The research showed the importance of parental assistance for the treatment continuation of children suffering from thalassemia major.